Análisis bibliométrico de la importancia de los páramos en el Ecuador en privación de servicios ecosistemicos 2018-2023. - Acuña Caisaguano, Mayra Lizeth (2023)
This research report analyzes and systematizes the characteristics of the Ecuadorian paramos, as well as the eco-systemic importance of the paramo at both the ecological and anthropic levels. The main objective is to obtain an extensive and updated vision of the situation of these ecosystems and the main challenges they face in the country. The methodology used is descriptive of bibliographic documentary character, since the work is emphasized in the collection, analysis, decoding and synthesis of the information found in different physical and digital works in the data available on the web and books both in the scientific and technical literature related to the moorlands in Ecuador, to use the mentioned methodology we considered an analysis with the software Overviewers in conjunction with research tools such as Scopus, Google Scholar, Scielo, Jane which gave us countless data for this research in that way a comprehensive analysis of the data and identify issues such as the most relevant trends related to the moors in Ecuador ,among them are key aspects such as the geographical distribution of the paramos in the country, their biological diversity and the factors that influence it, the impacts of climate change on these ecosystems, anthropogenic pressures and land use, conservation policies and strategies implemented, as well as research programs. This resulted in 1000 bibliographic documents with an index of 8039 citations, 2009.75 citations per year, 8.04 citations per document, 3.66 authors per article, making comparisons of authors and obtaining information relevant to the topic. The scientific advances of the moorlands in Ecuador in bibliometric research is focused on updating the main gaps in knowledge and to learn about priority areas in research to address them in future studies in this field.